Citrus Diseases Exotic to Florida: Powdery Mildew - Kuang-Ren Chung (EDIS)
Powdery mildew, which affects almost all citrus cultivars, is a common fungal disease problem in Asian countries. This 2-page fact sheet provides background information for this disease to provide a basis for evaluating potential risk to Florida citrus and for aiding decision-making to prevent its introduction and spread in Florida. It was written by K.-R. Chung and published by the UF Department of Plant Pathology, October 2011.